2009
DOI: 10.1093/ejo/cjp131
|View full text |Cite
|
Sign up to set email alerts
|

Patient and parent motivation for orthodontic treatment—a questionnaire study

Abstract: The aims of this investigation were to examine patients' and parents/guardians' motivation for seeking orthodontic treatment and to determine the influence of age and gender in this process. The sample comprised 674 subjects (365 girls and 309 boys) aged 7-18 years and 674 of their parents/guardians, as well as 86 adult patients aged 19-42 years (57 females and 29 males). Similar questionnaires, designed to assess motivation for orthodontic treatment, were completed by all subjects. Statistical analysis was un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
55
1
7

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(72 citation statements)
references
References 22 publications
3
55
1
7
Order By: Relevance
“…Ką kita savo studijoje nustatė Kilpelainen: net 73% tėvų pažymėjo odontologo patarimą dėl vaikų ortodontinio gydymo kaip motyvacinį veiksnį [5]. Panašūs rezultatai buvo gauti ir Daniels studijoje: didžiąją dalį pacientų ortodontiniam gydymui motyvavo odontologas, tačiau ne ką mažiau pacientų nusprendė patys [7]. Espeland nustatė, jog tėvai, kurie patys priėmė galutinį sprendimą dėl ortodontinio gydymo reikalingumo, galėjo turėti skirtingų motyvų dėl savo vaikų.…”
Section: Diskusijaunclassified
“…Ką kita savo studijoje nustatė Kilpelainen: net 73% tėvų pažymėjo odontologo patarimą dėl vaikų ortodontinio gydymo kaip motyvacinį veiksnį [5]. Panašūs rezultatai buvo gauti ir Daniels studijoje: didžiąją dalį pacientų ortodontiniam gydymui motyvavo odontologas, tačiau ne ką mažiau pacientų nusprendė patys [7]. Espeland nustatė, jog tėvai, kurie patys priėmė galutinį sprendimą dėl ortodontinio gydymo reikalingumo, galėjo turėti skirtingų motyvų dėl savo vaikų.…”
Section: Diskusijaunclassified
“…Optimal facial appearance is not only viewed as being more attractive but it is also more socially accepted by peers, teachers, employers and others. Smiling is still considered to be one of the most effective methods of influencing people [5]. Attractive people are perceived as friendly, intelligent, interesting, more social and much more positive personalities in general [2].…”
Section: Introductionmentioning
confidence: 99%
“…The child is then a target of jibes and is given nicknames and so forth [2]. Some individuals with dentofacial disharmonies who are seeking treatment usually experience some level of psychological distress that may warrant psychological intervention [5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, Rocha et al [10] showed that when the esthetic perception of smiles was evaluated by 160 dental students, there was a statistically significant difference between smiles with gingival recession and smiles without. This presents a problem because esthetics is a major motivational factor for patients to seek orthodontic treatment [11], [12]. For example, Reidman et al [11] showed that for 75% of patients seeking orthodontic treatment, dental esthetics was their primary motive.…”
mentioning
confidence: 99%